Who Gets a Childhood? Race and Juvenile Justice in Twentieth-Century Texas. (Politics and Culture in the Twentieth-Century South.). - Macleod, David I. (American Historical Review, 2012)
The article reviews the book "Who Gets a Childhood? Race and Juvenile Justice in Twentieth-Century Texas," by William S. Bush, part of the "Politics and Culture in the Twentieth-Century South" series.